Eben Smith: the dean of Western mining - Forsyth, David, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
Eben Smith, little-known in Colorado mining history. A successful fortune seeker who traveled to California during the gold rush. Moved to Colorado in 1860 with business partner Jerome Chaffee and involved in nearly every major mining camp. He was eulogized as "dean of mining in Colorado".--Provided by publisher.
Left Pennsylvania When I Was 19 -- One of Colorado's Headest Men -- David Moffat Set You on Your Feet -- I Handle All the Mining Business -- Our Various Operations -- Not a Pound of Ore in Sight -- I Cannot Pass a Good Mining Scheme By -- I Feel I Am in Hell's Hole -- The Dean of Mining in Colorado.
Keywords: Smith, Eben (Ebenezer), 1831-1906; Miners -- Colorado -- Cripple Creek -- Biography; Mining engineers -- Colorado -- Cripple Creek -- Biography; Gold mines and mining -- Colorado -- Cripple Creek -- Biography; Silver mines and mining -- Colorado -- Cripple Creek -- Biography; Mineral industries -- Colorado -- Cripple Creek -- Biography; Cripple Creek (Colo.) -- History -- 19th century